Respostas
respondido por:
3
2(3x + 1 ) + 5x = 0
6x + 2 + 5x = 0
6x + 5x = - 2
11x = - 2
x = - 2/11
6x + 2 + 5x = 0
6x + 5x = - 2
11x = - 2
x = - 2/11
respondido por:
1
Vc multipliva 2.(3x+ ou - 1) + 5x= 0
6x +\- 2 + 5x = 0
Ai vc passa o +\- 2 pro outro lado com o sinal contrario
6x + 5x = +/- 2
11x = +/- 2
Ai vc passa o 11 dividindo
X = +-2/11
6x +\- 2 + 5x = 0
Ai vc passa o +\- 2 pro outro lado com o sinal contrario
6x + 5x = +/- 2
11x = +/- 2
Ai vc passa o 11 dividindo
X = +-2/11
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás